DOCTORAL DISSERTATION OF POLITICAL SCIENCE UNDER MANIPUR UNIVERSITY: A CITATION ANALYSIS - Khwairakpam, Karina; Phuritsabam, Bobby; Sagolshem, Memori (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The article studies some part of my dissertation under Manipur University which investigates the citation patterns of Political Science PhD scholars to determine the kinds of information they rely on in their research. Having examined 26 PhD theses of Political Science completed within the years from 2000-2007 in the varsity, the study brings out 5 distinct aspects of citation. It analyses Authorship Pattern, Ranking of Journal, Country Wise Distribution and Publisher-specific citations of books. The collected data were analyzed using MS Excel software. Findings show a strong reliance on books weigh up to other form of sources, count on Indian literature and predominantly used “Economic and Political Weekly” as their reference. The study offers deep insights into the quality, relevance, and diversity of information obtained by scholars. Ultimately, such studies contribute to improving library services, guiding collection development, and informing future academic inquiries by identifying gaps, trends, and by serving as key contributors in a specific field.